The Strategic Role of Human Resource Management in the Tourism Industry - Wardhana, Zainal Firdaus; Sudiari, Made; Sengkey, Fenny (Jurnal Manajemen Pelayanan Hotel, 2024)
The tourism industry, as one of the most dynamic sectors globally, relies heavily on the effectiveness of human resource management (HRM) to maintain competitive advantage. This paper explores the strategic role of HRM in the tourism industry, emphasizing workforce planning, talent acquisition, training and development, and employee retention. By analyzing case studies and industry trends, the study highlights best practices and offers recommendations for optimizing HRM to enhance service quality and organizational performance. This research is qualitative descriptive, it utilized a comprehensive literature review to examine the current state of workforce planning and recruitment strategies in the tourism industry. To optimize HRM effectiveness, tourism organizations must adopt a data-driven, strategic approach to address key challenges, such as fluctuating demand, high employee turnover, and the need for continuous skills development. By implementing best practices in HRM, the tourism industry can unlock its full potential, providing exceptional experiences for travelers and contributing to the overall economic and cultural development of destinations worldwide.